Role of Lamin A/C Gene Mutations in the Signaling Defects Leading to Cardiomyopathies - Gerbino, Andrea; Procino, Giuseppe; Svelto, Maria; Carmosino, Monica (Frontiers in Physiology, 2018)
Nuclear lamin A/C are crucial components of the intricate proteic mesh that underlies the inner nuclear membrane and confers mainly nuclear and cytosolic rigidity. However, throughout the years a number of other key physiological processes have been associated with lamins such as modulation of both genes expression and the activity of signaling mediators. To further solidify its importance in cell physiology, mutations in the Lamin A/C gene (LMNA) have been associated to diverse pathological phenotypes with skeletal muscles and the heart being the most affected systems. When affected, the heart develops a wide array of phenotypes spanning from dilated cardiomyopathy with conduction defects to arrhythmogenic right ventricular cardiomyopathy. The surprising large number of cardiac phenotypes reflects the equally large number of specific mutations identified in the LMNA gene. In this this review we underlie how mutations in LMNA can impact the activity and the spatial/temporal organization of signaling mediators and transcription factors. We analyzed the everincreasing amount of findings collected in LmnaH222P/H222P mice whose cardiomyopathy resemble the most important features of the disease in humans and a number of key evidences from other experimental models. With this mini review we attempt to combine the newest insights regarding both the pathogenic effects of LMNA mutations in terms of signaling abnormalities and cardiac laminopathies.